2-C-Methyluridine modified hammerhead ribozyme against the estrogen receptor - Pontiggia, Rodrigo Martin (2010)
A new synthesis of 2′-C-methyluridine phosphoramidite is presented. Special emphasis is dedicated to the improvement of the protection of the tertiary 2′-hydroxyl group. Comparison to previous protecting strategies and analysis of stability under 5′-DMTr removing conditions are discussed. The synthetic incorporation of this modified nucleoside into the catalytic core of a hammerhead ribozyme against the estrogen receptor α protein (ER-α), and transfection experiments in MCF-7 cell line are also presented. © 2010 Elsevier Ltd. All rights reserved.